Male Mortality Trends in the United States, 1900-2010: Progress, Challenges, and Opportunities. (January 2020) - Jones, Wanda K.; Hahn, Robert A.; Parrish, R. Gibson; Teutsch, Steven M.; Chang, Man-Huei
Objectives: Male mortality fell substantially during the past century, and major causes of death changed. Building on our recent analysis of female mortality trends in the United States, we examined all-cause and cause-specific mortality trends at each decade from 1900 to 2010 among US males. Methods: We conducted a descriptive study of age-adjusted death rates (AADRs) for 11 categories of disease and injury stratified by race (white, nonwhite, and, when available, black), the excess of male mortality over female mortality ([male AADR − female AADR]/female AADR), and potential causes of persistent excess of male mortality. We used national mortality data for each decade. Results: From 1900 to 2010, the all-cause AADR declined 66.4% among white males and 74.5% among nonwhite males. Five major causes of death in 1900 were pneumonia and influenza, heart disease, stroke, tuberculosis, and unintentional nonmotor vehicle injuries; in 2010, infectious conditions were replaced by cancers and chronic lower respiratory diseases. The all-cause excess of male mortality rose from 9.1% in 1900 to 65.5% in 1980 among white males and a peak of 63.7% in 1990 among nonwhite males, subsequently falling among all groups. Conclusion: During the last century, AADRs among males declined more slowly than among females. Although the gap diminished in recent decades, exploration of social and behavioral factors may inform interventions that could further reduce death rates among males.